Effect of various levels of Ralgro on reproductive performance of yearling heifers - L. Corah; L.R. Sprott; G. Francis; G. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1980)
Implanting heifers at weaning time with 12, 24, or 36 mg of Ralgro did not affect reproductive performance of the heifers when bred as yearlings.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Reproductive performance; Yearling heifers